TRANSFORMATIVE DIGITAL LEARNING IN THE CONTEXT OF HIGHER EDUCATION: COMPARISON OF TRADITIONAL AND TRANSFORMATIVE CONCEPTS - Vindača, Olga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The topicality of the research problem is connected with transformative digital learning (TDL) in the context of higher education. The presence of technology in educational processes leads to a significant restructuring of the learning environment, promoting deep, strategic and personalized learning in lecturer-student collaborative teams, incorporating effective technology learning methods and learning to be based on new experiences and values creation. This article will review the issue of learning process in higher educational institutions focusing on traditional and transformative learning concepts. It is the preliminary result of on going applied research of RTA Research Institute for Regional Studies (RIRS).The aim of this article is to determine the necessity of learning process transformation in higher educational institutions analyzing proposals of experts from Latvian higher educational institutions and define the perspectives of TDL in the context of higher education. The research is based on two-part survey conducted for Latvian experts: 1) comparison of traditional and transformative learning concepts; 2) proposals for TDL perspectives and implementation. The results showed the necessity of learning process transformation, indicating the perspectives and its implementation problems.